Factors affecting green supply chain management in tourism industry, Investigation of Tehran’s Tour & Travel Agencies - mohammad rahim ramanian; pedram heydarnia kohan (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2012)
Tourism is widely recognized as an important economic sector. No matter what the economic climate, tourism has a significant impact on global and local economies. Tourism has been recognized as a complex system. Therefore, business management in the tourism industry critically needs to consider supply chain perspectives to integrate the fragmented nature of this industry. Moreover, development of tourism industry and its negative environmental impacts force companies to adopt sustainable strategies. This article reviews related literature and presents an analytical model in order to identify potential factors which influence the environmental strategic decision-making process. We investigated the influence of these potential factors on tourism industry and particularly on the travel agencies of Iran. Thus, analytical model was employed to design a questionnaire based on which 15 Tour & Travel agencies of Tehran were investigated through semi-structured interviews. The results show that in the absence of organizational benefits, external pressures could lead to GSCM adoption; also that implementation of this strategy is prone to get limited by strategic myopia and some other organizational factors.